Visualization of splenic marginal zone B cell shuttling and follicular B cell egress - Arnon, Tal I. (2012)
The splenic marginal zone (MZ) is a unique microenvironment where resident immune cells are exposed to the open blood circulation(1,2). Despite its importance in responses against blood-borne antigens, lymphocyte migration in the MZ has not been intravitally visualized due to challenges associated with achieving adequate imaging depth in this abdominal organ. Here we develop a 2-photon microscopy procedure to study MZ and follicular (FO) B cell movement in the live spleen. We show that MZ B cells are highly motile and exhibit long membrane extensions. MZ B cells shuttle between MZ and follicles with at least one fifth of the cells exchanging between compartments per hour, a behavior that explains their ability to rapidly deliver antigens from the open blood circulation to the secluded follicles. FO B cells also transit from follicles to MZ but unlike MZ B cells, they fail to undergo integrin-mediated adhesion, become caught in fluid flow and are carried into the red pulp. FO B cell egress via the MZ is sphingosine-1-phosphate receptor-1 (S1PR1)-dependent. This study shows that MZ B cells migrate continually between MZ and follicles and establishes the MZ as a site of S1PR1-dependent B cell exit from follicles. The work also shows how adhesive differences of closely related cells critically influences their behavior in the same microenvironment.